Rain shelter and open field cultivation of tropical cabbage (Brassica oleracea L. var. capitata): A comparison between F1 hybrids based on vegetative characteristics - Malu Kishorekumar; P. Indira; T. E. George; T. Pradeepkumar; S. Kannan (Innovations in Agriculture)
The study's goals were to find the perfect tropical cabbage hybrid for the plains and to examine whether it was feasible to grow cabbage both during the growing season and outside of it. The experiment was laid out in a Randomized Block Design with four replications. Four F1 hybrids namely NS183, NS43, NS35 and Disha were used for the study during off season (July-Oct) and on season (Oct-Jan). Protected conditions were provided using a rainshelter of 100m2 floor area. The results revealed that non-wrapping leaves which is a non-desirable trait in cabbage was less inside polyhouse during both seasons. Plant spread was more in rain shelter crop during off season and was maximum for NS43 which was on par with other varieties tested. During on-season NS35 recorded maximum plant spread under both growing conditions. NS43 and NS35 can be recommended for offseason and on season cultivation respectively. Rain shelter cultivation provides a conducive condition for the cultivation of an additional crop thereby providing extra income for the farmers.